1983
DOI: 10.1111/j.2042-3306.1983.tb01786.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus hyicus in skin lesions of horses

Abstract: Summary Staphylococcus hyicus (subspecies hyicus) was isolated as the only pathogenic organism from two independent cases of dermatitis of the lower parts of the limbs (grease heel) in horses. The organism was recovered together with other pathogenic staphylococci from similar conditions in two other horses of different origins. These conditions were characterised by epidermolysis, alopecia and crust formation. They responded quickly to antibiotic treatment. The organism was also isolated from a long standing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 4 publications
0
13
0
1
Order By: Relevance
“…Interestingly, there is evidence of equine AD flares in the summer . There are many similarities between the disease that occurs in humans and animals, and canine AD seems to be the most closely related to human AD .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there is evidence of equine AD flares in the summer . There are many similarities between the disease that occurs in humans and animals, and canine AD seems to be the most closely related to human AD .…”
Section: Discussionmentioning
confidence: 99%
“…The best‐characterized disease complex in animals associated with a CNS infection is exudative epidermitis in piglets, caused by S. hyicus (this species is sometimes referred to as belonging to the coagulase‐positive group). Sporadic reports of dermatitis where S. hyicus has been isolated among farm animals other than pigs have been published ( Devriese, 1979; Devriese et al, 1983). CNS are often isolated from superficial bacterial infections in cats and the predominating species, S. felis , is more or less host‐specific for cats ( Igimi et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…hyicus is known as the causal pathogen of exudative epidermites in pigs [21]. This is isolated from healthy or [3,4,20,21]. In this study, it was suggested that S. hyicus was closely related to dermatosis developing on the back, side, and chest regions.…”
Section: T Equinum Trichophyton Verrucosum Trichophyton Mentagrophmentioning
confidence: 91%
“…On the other hand, there have been few studies on the causes of infectious dermatosis other than dermatophytosis [3,4,15], and such a study has never been for racehorses. The purpose of this study was to clarify the microbiological causes of dermatosis in racehorses and to gather data on the diagnosis and treatment of the infectious dermatosis.…”
mentioning
confidence: 99%